Long-term respiratory outcomes after COVID-19: a Brazilian cohort study - Nina Rocha Godinho dos Reis Visconti; Michelle Cailleaux-Cezar; Domenico Capone; Maria Izabel Veiga dos Santos; Nadja Polisseni Graça; Luiz Paulo Pinheiro Loivos; Alexandre Pinto Cardoso; Fernanda Carvalho de Queiroz Mello (Pan American Health Organization, 2022)
Objective. To investigate the prevalence and risk factors for persistent symptoms up to 12 months after hospital discharge in COVID-19 survivors. Methods. This prospective cohort study included patients with COVID-19 discharged from a university hospital in Brazil. Follow-up was performed 2, 6, and 12 months after discharge. Lung function tests and chest computed tomography (CT) were performed 2 months after discharge and were repeated if abnormal. The primary outcomes were the symptoms present, work status, and limitations in daily activities. Results. Eighty-eight patients were included. Dyspnea (54.5%), fatigue (50.0%), myalgia, and muscle weakness (46.6%) were the most common symptoms, which decreased over time. Anxiety was frequent (46.6%) and remained unchanged. One year after discharge, 43.2% of the patients reported limitations in daily activities, and 17.6% had not returned to work. Corticosteroid use was significantly associated with dyspnea and limitations in daily activities. Females had an increased risk of fatigue at the 12-month assessment, with marginal significance after multivariable adjustment. Young age and bronchial wall thickening on admission CT were also risk factors for dyspnea at follow-up. The most common lung function abnormalities were reduced diffusion capacity and small airway disease, which partially improved over time. Conclusions. One year after hospital discharge, more than one-third of patients still had persistent COVID-19-related symptoms, remarkable dyspnea, fatigue, and limitations in daily activities, regardless of acute disease severity. Age, female sex, corticosteroid use during hospitalization, and bronchial thickening on admission CT were associated with an increased risk of sequelae.